Intermediaries and the International Obligation to Protect Child Witnesses in South Africa - Fambasayi, Rongedzayi; Koraan, René (Potchefstroom Electronic Law Journal, 2018)
This contribution examines the protection of child witnesses in criminal proceedings under international and regional laws. This consideration is made against the background that the Constitution of the Republic of South Africa, 1996 proclaims in section 39(1)(b) that in interpreting the Bill of Rights and any legislation a court or tribunal must consider international law. The United Nations Convention on the Rights of the Child (1989), the African Charter on the Rights and Welfare of the Child (1990) and the United Nations Guidelines on Justice for Child Victims and Witnesses to Crime (2005) do not make specific reference to child witnesses and how they should be treated. However, it is argued that the guiding principles enshrined therein provide for the protection of child witnesses, particularly the best interests of the child and the right to participate. In addition, the article enumerates and explains the rights of child witnesses as provided for in the UN Guidelines. International law will be discussed first, and then South African law, to establish if the international obligation to protect child witnesses is being adhered to.